Limit theorems in the theory of multipoint boundary-value problems - Nedokis, V. A.; Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We present a reduction of a countable system of differential equations with countably-point boundary conditions to the case of a finite-dimensional multipoint boundary-value problem. We separately consider the case of a linear system.